Konsep Akhlak Menurut KH Hasyim Asy’ari Dalam Kitab Adab Al-Alim Wa Al-Muta’alim - Astuti, Amrulloh Fuji; Ismail, Zulfikar; Hasanah, Tita (Ikatan Dai Indonesia, 2022)
The purpose of this study is to reveal the meaning of the concept of moral education according to KH Hayim Ash'ari in the book Adab al-Alim wa al-Muta'alim and its relevance to education today. This type of research is library research with deductive and inductive methods with the data collection tool is documentation and the data source consists of primary data, namely the book of Adab al-Alim wa al-Muta'alim by KH Hasyim Asy'ari and secondary data from other references. The results of the research and discussion, it is concluded that: Based on the discussion and analysis above, the researcher concludes that the concept of moral education in KH Hasyim Asy'ari contained in the book Adab al'Alim wa al-Muta'allim includes moral education for education and students. Moral values ​​emphasize the arrangement of the heart. These values ​​are more religious in nature, with strong Sufism nuances, and the basis is that every behavior is designed to approach and seek blessings from Allah SWT. Such as: straightening intentions, wara behavior, qonaah behavior, good use of time, being ta'dzim, tawadhu (humble), patient, establishing good cooperation, being istiqomah, likes to read, istiqomah (consistent), maintaining relationships, expanding knowledge , adab in asking questions, has the nature of affection, active, and diligent, polite to the teacher. KH Hasyim Asy'ari in the book Adab al-Alim wa al-Muta'allim on moral education related to education in Indonesia KH Hasyim Asya'ari in Adab al-Alim wa al Muta'allim Moral values ​​in the book prove this and can still be applied today, and can support the government initiated by the following institutions to strengthen moral education or character although the percentage in question is more religious, because the concept of moral education KH Hasyim Asy'ari is more inclined to the values ​​of Sufism.